A compendious study of online payment systems:Past developments, present impact, and future considerations - Khan, Burhan Ul Islam; Olanrewaju, Rashidah Funke; Baba, Asifa Mehraj; Langoo, Adil Ahmad; Assad, Shahul (The Science and Information Organization (SAI), 2017)
The advent of e-commerce together with the growth of the Internet promoted the digitisation of the payment process with the provision of various online payment methods like electronic cash, debit cards, credit cards, contactless payment, mobile wallets, etc. Besides, the services provided by mobile payment are gaining popularity day-by-day and are showing a transition by advancing towards a propitious future of speculative prospects in conjunction with the technological innovations. This paper is aimed at evaluating the present status and growth of online payment systems in worldwide markets and also takes a look at its future. In this paper, a comprehensive survey on all the aspects of electronic payment has been conducted after analysis of several research studies on online payment systems. Several online payment system services, the associated security issues and the future of such modes of payment have been analysed. This study also analyses the various factors that affect the adoption of online payment systems by consumers. Furthermore, there can be seen a huge growth in mobile payment methods globally beating both debit and credit card payments, all due to the convenience and security offered by them. Nevertheless, various obstacles have been identified in the adoption of online payment methods; thus, some measures have to be taken for granting this industry a hopeful future. Thus, there should be a suitable trade-off between usability and security when designing online payment systems in order to attract customers. Also, technical and organisational issues which arise in the attempt to achieve interoperability must be taken into consideration by the designers. As a matter of fact, the process of developing interoperable and flexible solutions and universal standards is one of the most difficult tasks in the future ahead.